CONFORMITY OF DSN-MUI FATWA REGARDING MURABAHAH AGREEMENT IN MULTI-BENEFIT IB FINANCING AT BTN SYARIAH KCPS KUDUS - Sadiyah, Khalimah; Wahidullah, Wahidullah; Utami, Cahyaning Budi (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of this study was to analyze the implementation of the murabahah contract on the Multimanfaat iB financing product at BTN Syariah KCPS Kudus, and its compliance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) No. 04/DSN-MUI/IV/2000. The method used in this study was a descriptive qualitative approach, data collection by interview, and observation. The results of the study indicate that the murabahah contract applied in this financing has adopted sharia principles, where the bank is the provider of goods and the customer is the buyer. However, there are challenges in its implementation, such as the lack of customer understanding of the contract mechanism and information transparency. The objects of financing that are traded are in accordance with sharia provisions, and the collateral system applied is different between general customers and BTN employees. Margin determination also varies based on the financing period. This study recommends increasing sharia financial literacy and evaluating information transparency to customers, as well as developing a more innovative murabahah contract scheme to improve the efficiency of sharia banking transactions.